The Phenomenon of Beauty Privilege as a Requirement in Job Vacancies - Sungkar, Neti Zunaida; Hakim, Lukman (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
The phenomenon of beauty privilege, an advantage gained by individuals based on their perceived socially attractive physical appearance, is often an implicit or explicit requirement in the job recruitment process in Indonesia. This study aims to explore public responses, particularly job seekers, to beauty privilege as a discriminatory practice that impacts employment opportunities and psychological well-being. Using a qualitative phenomenological approach, data were collected through in-depth semi-structured interviews with seven informants who are active users of platform X, as well as documentation of social media posts related to the issue of beauty privilege. Data analysis was conducted using the Miles and Huberman interactive model and source triangulation to increase validity. The results show that job seekers perceive physical appearance requirements in job openings as a form of discrimination unrelated to competency. The experience of appearance-based job rejections leads to psychological impacts such as low self-esteem and stress. Furthermore, public conversations on platform X reflect collective concerns about recruitment inequities. This study concludes that beauty privilege reinforces social bias in employment and recommends the implementation of inclusive recruitment policies and anti-bias training for recruiters to support equal employment opportunities.